EFEKTIVITAS PELAKSANAAN BIMBINGAN KLASIKAL DENGAN TEKNIK ROLE-PLAYING DALAM MENINGKATAN PERILAKU SOPAN SANTUN PADA.SISWA KELAS X TBO DI SMK N 1 SAMBIREJO TAHUN.PELAJARAN 2022/2023 - Sari, Dea Miranda Prastika (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: Knowing whether or not the Implementation of Classical Guidance with Role Playing Techniques in Improving Courtesy Behavior in Class X TBO Students at SMK N 1 SAMBIREJO in the 2022/2023 Academic Year is the aim of this study. This research is included in experimental or experimental quantitative research. In this study, the population used was 36 students of class X TBO SMK N 1 Sambirejo in the 2022/2023 academic year. Meanwhile, the saturated sampling technique is the sampling technique used in this research, where 36 students from the entire population were used as samples, therefore the sample in this study was all students of class X TBO SMK N 1 Sambirejo in the 2022/2023 academic year. Meanwhile, what was used as a trial was the class outside the sample, namely class X TB 1 SMKN I Sambirejo. Questionnaires and documentation are the techniques used in this research. After that, in order to test the hypothesis and analyze the data, the t-test was used in this study. After data analysis was carried out, data was obtained regarding the effectiveness of the implementation of classical guidance with role playing techniques in improving polite behavior in class X TBO students at SMK N 1 Sambirejo in the 2022/2023 academic year, obtained t-count = 9.016, then matched it to the t-test table where t-table at d.b = N-1 (36-1) = 35, which shows a significance level of 1% = 2.724 and 5% = 2.030. Based on this, it can be concluded that the t-count value is greater than the t-table at a significance level of 1% or 5%, where 2.724 < 9.016 > 2.030. Then it can be concluded that Ho which reads